Judicial Considerations and Policy Gaps in Combating Wildlife Trade Crime - Simanjuntak, Yemima Nurhayati; Lewerissa, Yanti Amelia; Tuhumury, Carolina (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Wildlife trade is a form of environmental crime that has serious impacts on biodiversity. Ambon City, as part of the Eastern Indonesia region which is rich in endemic species, is also a location for criminal acts of protected wildlife trade. This can threaten the survival of species and their ecosystems. Purposes of the Research: The purpose of this study is to examine and analyze the policy of combating wildlife trade in Ambon City, both in terms of penal (criminal law) and non-penal (non-criminal law) efforts, and to assess the basis for judges' considerations in imposing criminal sentences on perpetrators. This study uses a normative legal research method with a statutory approach and a conceptual approach. Methods of the Research: This research uses normative juridical using primary, secondary, and tertiary legal materials. The collection technique is done through literature studies in the form of books, scientific works, and other literature. Findings of the Research: This research shows that efforts to tackle wildlife trade crime in Ambon City are still very weak. Based on a study of two Ambon District Court decisions (No. 327/Pid.Sus-LH/2023/PN Amb and No. 242/Pid.Sus-LH/2024/PN Amb), it was found that law enforcement has not provided an optimal deterrent effect. The penalties imposed on perpetrators tend to be light and disproportionate to the environmental damage caused. This study also found that non-penal efforts such as legal education, environmental monitoring, and community empowerment have not been effective. In addition, public understanding of the law on wildlife protection is still low. Thus, a more integrative policy between penal and non-penal (preventive and educative) approaches is needed to effectively and sustainably tackle wildlife trade in Ambon City.